Developing Safety-Critical Software: A Practical Guide for Aviation Software and DO-178C Compliance - Rierson, Leanna (CRC Press, 2013)
As the complexity and criticality of software increase and projects are pressed to develop software faster and more cheaply, it becomes even more important to ensure that software-intensive systems are reliable and safe. This book helps you develop, manage, and approve safety-critical software more efficiently and effectively. Although the focus is on aviation software and compliance with RTCA/DO-178C and its supplements, the principles also apply to other safety-critical software. Written by an international authority on the subject, this book brings you a wealth of best practices, real-world examples, and concrete recommendations.